1999
DOI: 10.1006/viro.1999.9908
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Immunopathogenesis by SIV/HIV-1 (SHIV) Containing a Variant Form of the HIV-1sf33 env Gene in Juvenile and Newborn Rhesus Macaques

Abstract: SIV/HIV-1 (SHIV) chimeric clones, constructed by substituting portions of the pathogenic molecular clone SIVmac239 with counterpart portions from HIV-1 clones, provide a means to analyze functions of selected HIV-1 genes in vivo in nonhuman primates. Our studies focused on SHIVSF33, which contains the vpu, tat, rev, and env genes of the cytopathic, T-cell line tropic clone HIV-1sf33 (subtype-B); this clone has a premature stop codon in the vpu gene. In three juvenile macaques inoculated intravenously with SHIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…All viral stocks were quantitated for viral RNA by real-time reverse transcriptase-PCR (RT-PCR) (see below) and for SIV p27 gag by enzyme-linked immunosorbent assay (Beckman Coulter, Hialeah, Fla.). SHIV SF33A was prepared by passage in CEMX174 cells as previously described (28 Immunophenotypic characterization of peripheral blood lymphocytes was performed with a FACscan flow cytometer (BD Biosciences, San Jose, Calif.) together with monoclonal antibodies specific for CD3 (SP34), CD4 (M-T477), and CD8 (SK1), all obtained from BD Biosciences. Staining was performed with 50 l of whole blood or purified cells (10 6 to 10 7 /ml) in phosphate-buffered saline-0.5% bovine serum albumin.…”
Section: Viruses and Inoculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…All viral stocks were quantitated for viral RNA by real-time reverse transcriptase-PCR (RT-PCR) (see below) and for SIV p27 gag by enzyme-linked immunosorbent assay (Beckman Coulter, Hialeah, Fla.). SHIV SF33A was prepared by passage in CEMX174 cells as previously described (28 Immunophenotypic characterization of peripheral blood lymphocytes was performed with a FACscan flow cytometer (BD Biosciences, San Jose, Calif.) together with monoclonal antibodies specific for CD3 (SP34), CD4 (M-T477), and CD8 (SK1), all obtained from BD Biosciences. Staining was performed with 50 l of whole blood or purified cells (10 6 to 10 7 /ml) in phosphate-buffered saline-0.5% bovine serum albumin.…”
Section: Viruses and Inoculationsmentioning
confidence: 99%
“…Experimental infection of newborn Asian macaques with selected strains of simian immunodeficiency virus (SIV), or chimeric simian-human immunodeficiency virus (SHIV) causes a fatal AIDS-like disease that closely recapitulates the spectrum of disease in HIV-1-infected children (2,5,28,30). We selected two phenotypically distinct SHIV strains for in vivo studies in infant rhesus macaques: SHIV SF33A utilizes the CXCR4 coreceptor and produces a rapid decline of CD4 ϩ T cells in peripheral blood in both infant and adult macaques, and SHIV SF162P3 utilizes the CCR5 coreceptor and causes depletion of CD4 ϩ T cells in the gastrointestinal tract in adult macaques (14,28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies of SHIVs that use CXCR4 and the CCR5 coreceptor (X4 and R5 SHIVs, respectively) have revealed the role of tropism in the rate and localization of CD4 ϩ T-cell depletion (19). Pathogenic X4 SHIVs typically cause a severe depletion of CD4 ϩ T lymphocytes in blood and peripheral lymph nodes within 1 month of infection (14,21,27,36). Pathogenic isolates of dualtropic R5X4 SHIVs also cause rapid CD4 ϩ T-cell depletion (29,46,50), while pathogenic R5 SHIVs cause a more protracted decrease of peripheral CD4 ϩ T cells similar to that seen in SIVmac infection (18).…”
mentioning
confidence: 99%
“…Although HIV strains replicating in vitro often exhibit mutations that abrogate Vpu expression, in vivo the Vpu open reading frame remains intact (12). In addition, macaque models of simian-human immunodeficiency virus infections have shown that during the nonpathogenic stages of disease, the Vpu reading frame is often disrupted, but as the virus evolves and becomes more pathogenic, the Vpu reading frame is often found to be intact (24)(25)(26). Finally, HIV-1 infection of certain primary cells, such as terminally differentiated, nondividing macrophages, generally requires Vpu (2,33).…”
mentioning
confidence: 99%